Development of an integrated quantum light-matter interface - Mather, Bradley (2021)
This thesis details the work carried out to improve and develop a system capable of interfacing atoms and light through an optical fibre interface. It sports a transverse laser drilled through hole in which cold caesium-133 atoms are introduced. This system currently offers a high optical depth and the promise of scalability onto a larger waveguide chip platform. This thesis reports on the progress towards a light-matter interface, with a focus on improved fibre hole interfaces. Improved interfaces are measured which possess different hole sizes and geometries drilled into many varieties of fibres with the intention of minimising losses across the fibre hole. The fibre interface structural stability and the polarisation stability of the fibres are also measured along with fibre stability and polarisation stability. The groundwork of an EIT system implementation is also described. Finally, the preliminary analysis of a multi-waveguide photonic chip including waveguide gaps for the loading of cold atoms is presented. This work is carried out in pursuit of the longer term goal of introducing this more complex system into the main experimental chamber, replacing the fibre interface.